USH2A is a Meissner’s corpuscle protein necessary for normal vibration sensing in mice and humans - Schwaller, Fred; Bégay, Valérie; García-García, Gema; Taberner, Francisco J.; Moshourab, Rabih; McDonald, Brennan; Docter, Trevor; Kühnemund, Johannes; Ojeda Alonso, Julia Anai; Paricio-Montesinos, Ricardo; Lechner, Stefan; Poulet, James F. A.; et al. (Nature neuroscience, 2021)
Fingertip mechanoreceptors comprise sensory neuron endings together with specialized skin cells that form the end-organ. Exquisitely sensitive, vibration-sensing neurons are associated with Meissner’s corpuscles in the skin. In the present study, we found that USH2A, a transmembrane protein with a very large extracellular domain, was found in terminal Schwann cells within Meissner’s corpuscles. Pathogenic USH2A mutations cause Usher’s syndrome, associated with hearing loss and visual impairment. We show that patients with biallelic pathogenic USH2A mutations also have clear and specific impairments in vibrotactile touch perception, as do mutant mice lacking USH2A. Forepaw rapidly adapting mechanoreceptors innervating Meissner’s corpuscles, recorded from Ush2a−/− mice, showed large reductions in vibration sensitivity. However, the USH2A protein was not found in sensory neurons. Thus, loss of USH2A in corpuscular end-organs reduced mechanoreceptor sensitivity as well as vibration perception. Thus, a tether-like protein is required to facilitate detection of small-amplitude vibrations essential for the perception of fine-grained tactile surfaces.
Gesehen am 6.12.2023